PERANCANGAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI DATA KEPENDUDUKAN DESA DENGAN FRAMEWORK TOGAF ADM - endra suseno (Cloud Information, 2020)
Policies in a non profit oriented organization also prioritize customer service. The development of information systems and information technology will have an impact on improving the quality of service, this applies in government that manages the community, makes the government to build and develop information systems to help business activities, to achieve organizational goals and services for stakeholders especially those related to data , information, technology and applications. The development of this information system must be aligned with the direction of the organizational strategy (enterprise), but some cases of managing information systems do not do linear mapping, but in parallel this is caused by the readiness of technology and the ability of human resources in mastering science and technology.The objective is to design a village population enterprise architecture data in the form of a blueprint that includes business architecture, data architecture, and application architecture to support village business activities using the TOGAF framework. As for designing using the facilities provided by TOGAF, the Architecture Development Method (ADM) using 6 phases owned by ADM .. The results of this study are expected to make practical contributions for decision makers in village government in planning the information system architecture in village management according with the vision and mission set.